Orogastric lavage: a lifesaving procedure now forgotten. - Premalatha S; Nik Azlan NM; Maryam MF (Penerbit UKM, 2014)
Orogastric lavage has been performed since 200 years ago for intoxicated patients. Due to the risk that outweighs benefits it has fallen out of favour for the last decade. A teenage girl presented to Emergency Department with history of ingestion of a bottle of pesticide within the time frame before gastric emptying. The girl was resuscitated, intubated and orogastric lavage was performed. Fifty cc of the toxic substance was siphoned and antidote of the toxin was administered. She was admitted to the Intensive Care Unit, subsequently recovered and discharge five days later. Definitive airway management, proper technique, correct selection of patients and adequate monitoring are paramount to the success of orogastric lavage.